The impacts of climate change : a comprehensive study of physical, biophysical, social, and political issues - Letcher, T. M. (Trevor M.) (Elsevier, 2021)
"The Impacts of Climate Change: A Comprehensive Study of Physical, Biophysical, Social and Political Issues presents the very real issues associated with climate change and global warming and how it affects the planet and everyone on it. From a physical perspective, the book covers such topics as population pressures, food issues, rising sea-levels and coastline degradation, and health. It then goes on to present social impacts, such as humanitarian issues, ethics, adaptation, urban issues, local action, and socio-economic issues. Finally, it addresses the political impacts, such as justice issues and politics of climate change in different locations. By offering this holistic review of the latest impacts of climate change, the book helps researchers to better understand what needs to be done in order to move toward renewable energy, change societal habits, and move toward sustainable development."--